2023
DOI: 10.1007/s11356-023-27011-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of environmentally related technologies and revenue taxes in environmental degradation in OECD countries

Abstract: The current research study employed PMG (Pooled Mean Group) estimator to examine the impact of foreign direct investment in ows (FDI In ows), Trade Openness (TO), environmental-related technologies (ERTs), environmental-related tax revenues (ERTRs), and Economic growth (EG) on carbon dioxide (CO2) emission with a dataset of 36 OECD countries spanning from 1990 to 2020. Kao and Pedroni cointegration test results show that study variables are stationary at I(0) and I(I) that conform pooled mean group (PMG) panel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 134 publications
0
3
0
Order By: Relevance
“…Therefore, it is necessary to ensure a sustainable environment without any social and economic loss at the domestic level. Such outcomes are occupied with the findings of [ 25 , 88 , 89 ]. However, Bashir et al [ 25 ], described the key role of environmental policy in OECD economies and found the supportive role of environmental tax in environmental quality.…”
Section: - Results and Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to ensure a sustainable environment without any social and economic loss at the domestic level. Such outcomes are occupied with the findings of [ 25 , 88 , 89 ]. However, Bashir et al [ 25 ], described the key role of environmental policy in OECD economies and found the supportive role of environmental tax in environmental quality.…”
Section: - Results and Discussionmentioning
confidence: 99%
“…, Polat & Eş Polat (2018), AtayPolat & Ergün (2021) andMeireles et al(2021) for EU countries,Oral & Sayın (2015),Önder (2017),Akyol & Gül (2021) andFatima et al(2023) for OECD countries,Safi et al(2021) for G7 countries,Saqib et al(2023) for G10 countries,Doğan et al(2022) for the 25 countries with the highest environmental performance index value,Meng et al(2013) for Australia,Kiuila et al(2019) for the Czech Republic andDoğan et al. (…”
mentioning
confidence: 99%
“…,Akbelen (2019),Uyduranoğlu & Öztürk (2020),Şimşek & Kesbiç (2020), AtayPolat & Ergün (2021),Akkaya & Hepsag (2021),Meireles et al(2021),Akyol & Gül (2021),Doğan et al(2022),Doğan et al(2023),Özbek (2023), Fatima et al(2023), Saqib et al(2023.…”
mentioning
confidence: 99%